(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The research aims to know the role that computerized accounting systems play in reducing financial risks according to the COSO framework. As this was achieved by analyzing spending on computerized accounting tools such as electronic devices and information networks, as well as conducting an analysis to measure financial risks according to the matrix provided by the COSO committee in a sample of Iraqi banks listed on the stock market for the fiscal period (2018-2019 -2020) and through that analysis, the research hypothesis was tested and its objectives were achieved.